Degradation of Tartrazine Using Hydrodynamic Cavitation‐Based Hybrid Techniques and Fenton Chemistry. Issue 6 (28th April 2022) - Gawande, Gayatri D.; Pinjari, Deepak V.; Chavan, Prakash V.
Abstract: Degradation of the tartrazine was investigated systematically using the Fenton oxidation process and hydrodynamic cavitation (HC)‐based hybrid techniques. The operating parameters, such as the inlet pressure, the initial pH, the initial concentration of tartrazine, and the molar ratio of the Fenton reagents, were optimized. A maximum degradation of 12.50 % was observed using HC alone at 5 bar pressure and a solution pH of 2, while Fenton chemistry showed 92.40 % degradation at a Fe 2+ /H2 O2 molar ratio of 1:36. HC in conjugation with H2 O2 or Fenton reagents showed maximum degradation values of 92 and 96.40 %, respectively. The degradation follows a pseudo‐first‐order kinetics with respect to the concentration of tartrazine, for Fenton chemistry and the HC‐based hybrid techniques. Abstract : Degradation of tartrazine was performed using hydrodynamic cavitation (HC)‐based hybrid methods and the Fenton oxidation process. The parameters for maximum tartrazine degradation were identified. HC combined with the Fenton reagent was found to be the most energy‐efficient oxidation process as compared to all other oxidation processes investigated.